Dynamics of Double Chaos - Ahmed, A. M.; Noori, S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
stract This paper includes studying (dynamic of double chaos) in two steps: First Step:- Applying ordinary differential equation have behaved chaotically such as (Duffing’s equation) on (double pendulum) equation system to get new system of ordinary differential equations depend on it next step. Second Step:- We demonstrate existence of a dynamics of double chaos in Duffing’s equation by relying on graphical result of Poincare’s map from numerical simulation.